Oxide-encapsulated silver NPs embedded in polymer for improved optical absorption - Goh, Wei Peng (2017)
Enhanced electric fields associated with surface plasmons can enhance light absorption in the surrounding medium that the plasmonic materials are embedded in. The exploitation of these unique properties in organic solar cells is well documented. Organic solar cells suffer from inherently low photo current and surface plasmons have the ability to overcome this drawback by improving absorption in the semiconducting photoactive layer. As surface plasmons manifest in the immediate vicinity of the plasmonic nanostructures, their placement in the polymeric active layer (or at least in close proximity to the active layer) is preferred. As the nanostructures are usually metallic in nature, embedding them in the semiconducting layer may introduce recombination sites. This can be circumvented by introducing a thin continuous insulating shell around the nanostructures. An insulating encapsulation layer helps in isolating nanostructures from the polymer layer, hence, mitigating' charge recombination. In this thesis, the effect on optical enhancement in a polymer by embedding 50 nm Ag nanoparticles (NPs) encapsulated with various oxides is investigated. The focus will be placed on the use of aluminum oxide (Ab03), hafnium oxide (Hf02), molybdenum oxide (Mo03) and silicon oxide (Si02). Modelling studies reveal that, at silver (Ag) NP resonance, optical enhancement in poly(3-hexythiophene ):phenyl-C61-butyric acid methyl ester (P3HT:PCBM) depends primarily on the position of peak extinction cross section relative to the polymer absorption. Photoinduced absorption (PIA) studies show an increased polaron yield when Ag NPs are protected with a sheath of Ab03. In fact, an optimal Ab03 thickness of 3 - 5 nm exists to generate maximum polaron concentration. At this range, absorption enhancement within the polymer film by the plasmonic electric field and the spatial separation of charge carriers from recombination centers are balanced. Absorption gains/losses in the photoactive layer are examined by calculating with reference to AM 1.5G solar spectrum. Through the additional use of simulation models, it is divulged that overall absorption in the polymer can be improved by incorporating oxide-encapsulated Ag NPs. Assuming a continuous shell is sufficient in mitigating charge recombination, a 2 nm thickness, regardless of the choice of oxide, should be enough to induce optical enhancement in the polymer with respect to a control P3HT:PCBM.